Carbide-derived carbon as well as preparation method and application thereof
By mixing transition metal carbide with MClx and heat treatment, carbide-derived carbon was prepared, with moderate graphitization and short preparation period, which solved the problem of low graphitization and long preparation period in the prior art, and improved its performance in the fields of electrochemistry and gas storage.
Patent Information
- Application Number
- CN202411989829.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
AI Technical Summary
The existing carbide-derived carbon has low graphitization degree and long preparation period, which limits its further development and application in the fields of electrochemistry and gas storage.
By mixing the transition metal carbide with MClx, putting it in a closed container, heating and melting under air conditioning, obtaining an intermediate and post-treatment to obtain a carbide-derived carbon, the ID/IG value in the Raman spectrum is 0.29-0.97.
The preparation cycle is shortened and a moderate degree of graphitization is obtained, which improves the performance of carbide-derived carbon in the fields of electrochemistry and gas storage.
Smart Images

Figure CN119898751A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon material preparation, and in particular to carbide-derived carbon and a preparation method and application thereof. Background Art
[0002] Carbide-derived carbon (CDC) is a product obtained by removing non-carbon elements from carbides or carbon-containing alloys. It has good prospects in electrochemistry and gas storage due to its adjustable pores and high specific surface area. At present, the main synthesis methods of carbide derivatives are halogen etching, acid etching, vacuum pyrolysis, molten salt thermal electrolysis, etc. These methods generally synthesize low degrees of graphitization and long preparation cycles, which limits the further development and application of carbide-derived carbon. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a method for preparing carbide-derived carbon, wherein the method has a short preparation period and the obtained carbide-derived carbon has a moderate degree of graphitization.
[0004] To this end, the first aspect of the present invention provides a method for preparing carbide-derived carbon, comprising: reacting a transition metal carbide with MCl x The mixture is mixed, placed in a sealed container, and heated to melt in an airtight condition to obtain an intermediate, wherein M comprises one or more of Fe, Ni and Zn, and x=2-3; the intermediate is post-treated to obtain carbide-derived carbon, and the ID / IG value of the carbide-derived carbon in the Raman spectrum is 0.29-0.97.
[0005] The method for preparing carbide-derived carbon proposed by the present invention comprises the following steps: x Mix, place in a sealed container, heat and melt under airtight conditions, MCl x It can provide a molten salt environment to convert the transition metal in the transition metal carbide into the chloride salt of the transition metal, and MCl x The M ions in the transition metal carbide can oxidize the transition metal elements in the transition metal carbide, playing a dealloying role. The M element can also serve as a graphitization catalyst, further promoting the graphitization of the carbide-derived carbon, so that it has a reasonable degree of graphitization. In summary, the method proposed in this application has a short preparation cycle, and the degree of graphitization of the obtained carbide-derived carbon is moderate.
[0006] In some embodiments of the present invention, the transition metal carbide includes one or more of molybdenum carbide, nickel carbide, and chromium carbide.
[0007] In some embodiments of the present invention, the MCl xIncludes one or more of FeCl3, NiCl2 and ZnCl2.
[0008] In some embodiments of the present invention, the transition metal carbide and MCl x Mix by grinding.
[0009] In some embodiments of the present invention, the MCl x Including FeCl3.
[0010] In some embodiments of the present invention, the transition metal carbide and MCl x The mass ratio is 1:(1-10).
[0011] In some embodiments of the present invention, the transition metal carbide and MCl x The mass ratio is 1:(2.5-5).
[0012] In some embodiments of the present invention, the heating temperature is 400°C-700°C.
[0013] In some embodiments of the present invention, the heating temperature is 600°C-700°C.
[0014] In some embodiments of the present invention, the heating time is 2h-6h.
[0015] In some embodiments of the present invention, the heating rate is 5°C / min-10°C / min.
[0016] In a second aspect of the present invention, the present invention provides a carbide-derived carbon, wherein the carbide-derived carbon is prepared by the method described in the first aspect of the present invention, and the ID / IG value of the carbide-derived carbon in the Raman spectrum is 0.29-0.97. The carbide-derived carbon provided by the present invention has excellent performance.
[0017] In the third aspect of the present invention, the present invention provides a battery, the battery comprising the carbide-derived carbon prepared by the method described in the first aspect of the present invention, or the carbide-derived carbon described in the second aspect. Therefore, the battery provided by the present invention has excellent performance.
[0018] In some embodiments of the present invention, the first charge specific capacity of the battery is 259mAh / g-319.5mAh / g; and / or, the first discharge specific capacity of the battery is 303mAh / g-351mAh / g; and / or, the first cycle coulombic efficiency of the battery is 80%-91%.
[0019] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0021] Figure 1 The Raman spectra of the carbide-derived carbon prepared in Example 1, Example 3 and Comparative Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0022] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0023] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0024] In a first aspect of the present invention, the present invention provides a method for preparing carbide-derived carbon, comprising:
[0025] S1. Combine transition metal carbides with MCl x The mixture is mixed, placed in a sealed container, and heated to melt in an airtight condition to obtain an intermediate, wherein M includes one or more of Fe, Ni and Zn, and x=2-3.
[0026] The reaction process of step S1 is as follows:
[0027] QC+aMCl x →aMCl x-1+ QCl a +C, where a depends on the valence state of Q in the carbide.
[0028] Among them, carbide QC itself acts as a reducing agent, and chloride MCl x is an oxidant, wherein Q is at least one of molybdenum, nickel and chromium.
[0029] As an example, x could be 2, 3, etc.
[0030] In some embodiments of the present invention, the transition metal carbide includes one or more of molybdenum carbide, nickel carbide and chromium carbide. The transition metal element in the transition metal carbide of the above material is easily oxidized by M ions, which plays a role of dealloying, thereby obtaining pure carbide-derived carbon.
[0031] In some embodiments of the present invention, the MCl x The salts include one or more of FeCl3, NiCl2 and ZnCl2, which can provide a molten salt environment to convert the transition metal in the transition metal carbide into a chloride salt of the transition metal, and MCl x The M ions in the transition metal carbide can oxidize the transition metal element in the transition metal carbide, playing a dealloying role. The M element can also serve as a graphitization catalyst, further promoting the graphitization of the derived carbon. In other embodiments of the present invention, the MCl x Including FeCl3.
[0032] In some embodiments of the present invention, the transition metal carbide and MCl x The mass ratio of transition metal carbides to MCl is 1: (1-10), for example, 1: 1, 1: 2.5, 1: 3, 1: 5, 1: 7, 1: 10, etc. x The mass ratio of M ions to MCl is controlled within the above range, and the M ions are sufficient to oxidize the transition metal elements in the transition metal carbide to play a dealloying role, and are sufficient to act as a graphitization catalyst to further promote the graphitization of the carbide-derived carbon, and will not introduce too many M ions to affect the purity of the carbide-derived carbon. As a result, the preparation cycle of the carbide-derived carbon is short, and the degree of graphitization of the obtained carbide-derived carbon is moderate. In other embodiments of the invention, the transition metal carbide and MCl x The mass ratio is 1:(2.5-5).
[0033] In some embodiments of the present invention, the transition metal carbide and MCl x Mix by grinding. Grinding can make transition metal carbides and MCl x The two are fully mixed and reacted fully, the preparation cycle of the carbide-derived carbon is short, and the degree of graphitization of the obtained carbide-derived carbon is moderate.
[0034] In some embodiments of the present invention, the heating temperature is 400°C-700°C. For example, the heating temperature can be 400°C, 500°C, 600°C, 700°C, etc. By controlling the heating temperature within the above range, the transition metal carbide and MCl can be x Heating to a molten state and forming a supercritical state is conducive to the transition metal carbide and MCl xThe reaction is sufficient, the uniformity of the generated carbide-derived carbon is improved, the preparation cycle of the carbide-derived carbon is short, and the degree of graphitization of the obtained carbide-derived carbon is moderate. In other embodiments of the present invention, the heating temperature is 600°C-700°C.
[0035] In some embodiments of the present invention, the heating time is 2h-6h. For example, the heating time can be 2h, 3h, 4h, 5h, 6h, etc. The heating time can be controlled within the above range to make the transition metal carbide and MCl x The reaction is sufficient, the uniformity of the generated carbide-derived carbon is improved, the preparation cycle of the carbide-derived carbon is short, and the degree of graphitization of the obtained carbide-derived carbon is moderate.
[0036] In some embodiments of the present invention, the heating temperature rise rate is 5°C / min-10°C / min. For example, it can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc. By controlling the heating rate within the above range, the two can be fully mixed and reacted, the preparation cycle of the carbide-derived carbon is short, and the degree of graphitization of the obtained carbide-derived carbon is moderate.
[0037] S2. Post-treating the intermediate to obtain carbide-derived carbon. In the Raman spectrum of the carbide-derived carbon, the ID / IG value is 0.29-0.97.
[0038] In some embodiments of the present invention, the post-treatment includes water washing, filtration, drying, etc.
[0039] As an example, in the Raman spectrum of the carbide-derived carbon, the ID / IG value may be 0.29, 0.3, 0.5, 0.7, 0.9, 0.97, etc., preferably 0.31-0.58.
[0040] The method for preparing carbide-derived carbon proposed by the present invention comprises the following steps: x Mix, place in a sealed container, heat and melt under airtight conditions, MCl x It can provide a molten salt environment to convert the transition metal in the transition metal carbide into the chloride salt of the transition metal, and MCl x The M ions in the transition metal carbide can oxidize the transition metal element in the transition metal carbide, playing a dealloying role. The M element can also serve as a graphitization catalyst, further promoting the graphitization of the carbide-derived carbon. In summary, the method proposed in the present invention has a short preparation cycle, and the obtained carbide-derived carbon has a suitable degree of graphitization.
[0041] In a second aspect of the present invention, the present invention provides a carbide-derived carbon, wherein the carbide-derived carbon is prepared by the method described in the first aspect of the present invention, and the ID / IG value of the carbide-derived carbon in the Raman spectrum is 0.29-0.97. The carbide-derived carbon provided by the present invention has excellent performance.
[0042] In the third aspect of the present invention, the present invention provides a battery, the battery comprising the carbide-derived carbon prepared by the method described in the first aspect of the present invention, or the carbide-derived carbon described in the second aspect. Therefore, the battery provided by the present invention uses the carbide-derived carbon with a suitable degree of graphitization as the negative electrode active material and has excellent performance.
[0043] In some embodiments of the present invention, the first charge specific capacity of the battery is 259mAh / g-319.5mAh / g, for example, it can be 259mAh / g, 270mAh / g, 290mAh / g, 300mAh / g, 310mAh / g, 319.5mAh / g, etc. Therefore, the first charge specific capacity of the battery proposed in the present invention is relatively high.
[0044] In some embodiments of the present invention, the first discharge specific capacity of the battery is 303mAh / g-351mAh / g, for example, it can be 303mAh / g, 310mAh / g, 320mAh / g, 330mAh / g, 340mAh / g, 350mAh / g, 351mAh / g, etc. Therefore, the first discharge specific capacity of the battery proposed in the present invention is relatively high.
[0045] In some embodiments of the present invention, the first cycle coulombic efficiency of the battery is 80%-91%, for example, 80%, 82%, 85%, 90%, 91%, etc. Therefore, the first cycle coulombic efficiency of the battery proposed by the present invention is relatively high.
[0046] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time allow ions (such as lithium ions, sodium ions, etc.) to pass through.
[0047] It can be understood that in the embodiments of the present invention, the materials and preparation methods used for the positive electrode plate, the negative electrode plate, the electrolyte and the isolation membrane can use materials and methods known in the art, which will not be described in detail here.
[0048] In some embodiments of the present invention, the battery includes a sodium ion battery. For a specific sodium ion battery, the embodiment of the present invention uses the carbide-derived carbon described in the first aspect as the negative electrode active material of the sodium ion battery, and the degree of graphitization of the negative electrode active material is moderate (ID / IG value is between 0.29-0.97, preferably 0.31-0.58, for example, it can be 0.29, 0.3, 0.5, 0.7, 0.9, 0.97, etc.), so that the various defects of the carbide-derived carbon are moderate, and these defects are conducive to the storage of sodium ions as active sites, showing that the battery has a high first-cycle discharge capacity, and the defects are not too many to increase the irreversible capacity of the negative electrode active material, so that the battery has a low first-cycle charging capacity and a low first efficiency; while the degree of graphitization of the carbide-derived carbon is too high, the order of the carbon is high, but the radius of the sodium ion is larger than that of the lithium ion, which is disadvantageous when embedding and extracting the carbide-derived carbon. The sodium meter line is less embedded and less extracted, so that the discharge capacity and charging capacity of the battery are low, and the first efficiency is high.
[0049] In some embodiments of the present invention, in the Raman spectrum of the carbide-derived carbon, the ID / IG value is 0.29-0.97. Preferably, it is 0.31-0.58, for example, it can be 0.29, 0.3, 0.5, 0.7, 0.9, 0.97, etc., so that the various defect contents of the carbide-derived carbon are moderate, and these defects are beneficial to the storage of sodium ions as active sites, showing that the battery has a high first-cycle discharge capacity, and the defects are not too many to increase the irreversible capacity of the negative electrode active material, thereby making the battery low in the first cycle charge capacity and low in the first efficiency; and the defects are not too few to cause difficulty in the insertion and removal of sodium ions, affecting the capacity and first efficiency of the battery.
[0050] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.
[0051] Example 1
[0052] First, 0.5 g of molybdenum carbide and 2.5 g of anhydrous ferric chloride were ground evenly in a mortar and placed in a high-pressure reactor, and then heated to 400°C at 5°C / min in a crucible furnace and kept warm for 5 hours. The obtained product was then washed with water, filtered, and placed in an oven at 80°C for drying to obtain carbide-derived carbon.
[0053] The preparation methods of Examples 2-7 and Comparative Example 1 are basically the same as those of Example 1, except that the parameters of the preparation process are different, see Table 1 for details.
[0054] Table 1
[0055]
[0056]
[0057] The Raman spectra of the carbide-derived carbon obtained in Examples 1 and 3 and Comparative Example 1 are as follows: Figure 1 As shown in the figure, it can be seen that the carbide-derived carbon of Examples 1 and 2 is at 1500 cm -1 -1750cm -1 and 2500cm -1 -2750cm -1 There is a strong peak between the two, indicating that the degree of graphitization of the obtained carbide-derived carbon is high.
[0058] The degree of graphitization of the carbide-derived carbon prepared in Examples 1-7 and Comparative Example 1 was determined by the following test method:
[0059] According to Raman spectroscopy, the G peak usually appears at 1580cm -1 The intensity and shape of the G peak can reflect the topological structure of the sample. The intensity of the G peak is related to the integrity of the carbon material lattice, that is, it represents the degree of graphitization of the carbon material; the D peak usually appears at 1300cm -1 The D peak in the carbon material indicates the presence of structural defects or disorder in the material. The intensity of the D peak is proportional to the defect density in the material. Therefore, the degree of graphitization of the carbon material can be directly reflected by ID / IG, which is the intensity ratio or area ratio of the D peak and the G peak, where I represents Intensity. -1 The nearby 2D peak is caused by the phonon transition of carbon atoms with reverse momentum, which is related to the degree of graphitization and the number of layers of the carbon material.
[0060] It can be seen from the data ID / IG in Table 1 that the degree of graphitization of the carbide-derived carbon prepared in the embodiment of the present invention is moderate.
[0061] The carbide-derived carbons of Examples 1-7 and Comparative Example 1 were used as negative electrode active materials to assemble sodium ion batteries, and the performance of the batteries was measured to obtain Table 2, wherein the carbon material and carboxymethyl cellulose were weighed in a certain ratio of 90:10-95:5, added with an appropriate amount of deionized water and then ball-milled for 2 hours using a planetary ball mill, the ball-milled slurry was coated on a current collector, and after vacuum drying at 80°C for 12 hours, it was cut into negative electrode sheets with a diameter of 12 mm, metallic sodium was used as the counter electrode and reference electrode, a glass fiber diaphragm was used as the diaphragm, a NaPF6 with a concentration of 1 mol / L was used as the electrolyte, and a mixed solution of diethyl carbonate and ethylene carbonate (volume ratio of 1:1) was used as the solvent, and the button batteries were assembled in a glove box with an argon atmosphere. The specific electrochemical performance test is as follows: On the Xinwei test system, the assembled button battery is charged and discharged in a constant current charge and discharge mode, the voltage window is set to 0-2V, and the test current density is 0.1C (1C=100mA / g), that is, a current density of 10mA / g is used for charge and discharge tests, first discharging to 0V at 0.1C, and then charging to 2V at 0.1C, wherein the discharge capacity is denoted as C1, and the charging capacity is denoted as C2, and the first coulombic efficiency is calculated as C2 / C1×100%, and Table 2 is obtained. It can be seen from Table 2 that the carbide-derived carbon prepared in the present application has excellent performance when used in batteries.
[0062] Table 2
[0063]
[0064] In summary, the method for preparing carbide-derived carbon proposed in the present invention has a short preparation period, and the obtained carbide-derived carbon has a moderate degree of graphitization.
[0065] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0066] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing carbide-derived carbon, characterized in that: include: Transition metal carbides and MCl x Mixing, placing in a sealed container, heating and melting in an airtight condition to obtain an intermediate, wherein M comprises one or more of Fe, Ni and Zn, and x=2-3; The intermediate is post-treated to obtain carbide-derived carbon, and in the Raman spectrum of the carbide-derived carbon, the ID / IG value is 0.29-0.
97.
2. The method according to claim 1, characterized in that The transition metal carbide comprises one or more of molybdenum carbide, nickel carbide and chromium carbide; and / or, The MCl x Includes one or more of FeCl3, NiCl2 and ZnCl2.
3. The method according to claim 1 or 2, characterized in that: The transition metal carbide and MCl x Mixing by grinding; and / or, The MCl x Including FeCl3.
4. The method according to claim 1 or 2, characterized in that: The transition metal carbide and MCl x The mass ratio is 1:(1-10).
5. The method according to claim 1 or 2, characterized in that: The transition metal carbide and MCl x The mass ratio is 1:(2.5-5).
6. The method according to claim 1 or 2, characterized in that: The heating temperature is 400°C-700°C.
7. The method according to claim 1 or 2, characterized in that: The heating temperature is 600°C-700°C.
8. The method according to claim 1 or 2, characterized in that: The heating time is 2h-6h; and / or, The heating rate is 5°C / min-10°C / min.
9. A carbide-derived carbon, characterized in that: The carbide-derived carbon is prepared by the method according to any one of claims 1 to 8, and in the Raman spectrum of the carbide-derived carbon, the ID / IG value is 0.29-0.
97.
10. A battery, characterized in that: The battery comprises the carbide-derived carbon prepared by the method of any one of claims 1 to 8 or the carbide-derived carbon of claim 9; The first charge specific capacity of the battery is 259mAh / g-319.5mAh / g; The first discharge specific capacity of the battery is 303mAh / g-351mAh / g; The first cycle coulombic efficiency of the battery is 80%-91%.